How to understand nested lambda functions in Haskell - haskell

I am trying to understand the meaning of the following 2 lambda expressions in Haskell:
f = \x -> x (\y -> x y)
g = \x -> (\y -> y) x
I tried to convert them, and I got this:
f x y = x x y
g x y = y x
Is this correct? I assumed the arguments of both functions have to be x and y, as they are both found in a lambda expression in the function description. I basically understood it this way: f(x) = x f(y) and f(y) = y x. And for g, g(x) = g(y) x and g(y) = y. But as I am new to Haskell, I'm not very confident with these types of conversion. If not correct, what would be a correct conversion?

Neither is correct. Your solution uses the functions
f x y = x x y
g x y = y x
which actually mean
f = \x -> (\y -> x x y)
g = \x -> (\y -> y x)
and those differ from the original expressions
f = \x -> x (\y -> x y)
g = \x -> (\y -> y) x
The above two equations can be rewritten as
f x = x (\y -> x y)
g x = (\y -> y) x
But from here, there is no way to turn the remaining lambdas into more arguments for f or g. At best, we can simplify them using beta/eta conversion and get
f x = x x -- eta (\y -> x y) = x
g x = x -- beta (\y -> y) x = x
(Also see the comment below by Will Ness, who points out that through an additional eta expansion in f we could reach the OP's definition. Still, that is incidental.)
Finally, note that Haskell will not accept f x = x x since that can not be typed, unless we use rank-2 types and explicitly provide a type annotation like f :: (forall a. a) -> b. The original code f = \x -> x (\y -> x y) suffers from the same issue. That would also be fine in untyped languages, e.g. the untyped lambda calculus in programming languages theory.

The :type command at the GHCi prompt is your friend. Let's take your second example first
λ> :type let g = \x -> (\y -> y) x in g
let g = \x -> (\y -> y) x in g :: p -> p
So g is well-typed and is a convoluted way to write an identity function :: p -> p. Specifically, g takes some x and applies an identity function (\y -> y) to x, resulting in x. GHCi in giving the type uses a fresh type name p, to avoid confusion. No your g x y = ... is not equivalent. (Check it with :type.)
You can abbreviate :type to just :t. Then let's take your first example.
λ> :t let f = \x -> x (\y -> x y) in f
* Occurs check: cannot construct the infinite type: t2 ~ t2 -> t3
* In the first argument of `x', namely `(\ y -> x y)'
In the expression: x (\ y -> x y)
In the expression: \ x -> x (\ y -> x y)
* Relevant bindings include
x :: t2 -> t3 (bound at <interactive>:1:10)
f :: (t2 -> t3) -> t3 (bound at <interactive>:1:5)
Errk. Is your suggested f the same as that?
λ> :t let f x y = x x y in f
* Occurs check: cannot construct the infinite type:
t3 ~ t3 -> t4 -> t5
* In the first argument of `x', namely `x'
It at least looks like a similar error message. What are these t2, t3, t4, t5? Again it's GHCi using fresh names for the types, to avoid confusion.
Looking at the let f = ..., GHCi sees x is applied to something, so it gives x :: t2 -> t3 where t2 is the type of its argument, t3 is the return type. It also sees f = \x -> x (blah). So the return type of f must be whatever x returns, i.e. t3, and the argument to f is x. So f :: (t2 -> t3) -> t3.
Inside the (blah), there's x applied to something. So the something (i.e. y) must be the type of x's argument, and the return type must be x's return type. I.e. (\y -> x y) :: t2 -> t3. Errk: then we must have x's argument type same as that, because x is applied to it. And the way we write 'same as' is with ~.
Then the error message tells you GHCi is trying to make sense of t2 ~ (t2 -> t3). (-> binds tighter than ~.) And if you try to subsitute that equivalence for t2 into the RHS you'll get t2 ~ (((... -> t3) -> t3)-> t3) ad infinitum.
Your suggested equivalent for f x y = is not equivalent (the message/typing is a little different). But they're both infinite types, so not allowed.

Related

Meaning of (\x y z -> x y z) in Haskell

In understand the meaning and the type of (\x y z -> x+y+z) for example. The type of (\x y z -> x y z)is (t1 -> t2 -> t3) -> t1 -> t2 -> t3. But what does that mean and why are now round brackets in the type?
In Haskell, something of the form a b c (i.e., juxtaposition of letter-names without infix symbols between them) generally means a is a function and being applied to b and c.In this case, x y z is basically what in other languages would be written x(y,z). In Haskell, you can also write it
\x y z -> x(y)(z)
or in fact (x)(y)(z) or ((x)y)z, but parentheses are discouraged unless needed.
So knowing that, it's clear that the type of the first argument of that lambda, i.e. of x, needs to be a function type. In this case, a function taking two arguments of whatever type y and z happen to be, respectively. I.e.
(\x y z -> x y z) :: (typeofy -> typeofz -> resulttype) -> ...
└───────── type of x ────────────┘
Now say y :: t1 and z :: t2 and the final result should be t3, and we have
(\x y z -> x y z) :: (t1 -> t2 -> t3) -> (t1 -> t2 -> t3)
└─ type of x ──┘ └y └z └(x y z)
Function-arrows are right-associative, i.e. the parentheses on the right side of the type can be omitted:
(\x y z -> x y z) :: (t1 -> t2 -> t3) -> t1 -> t2 -> t3
└─ type of x ──┘ └y └z └(x y z)
The parentheses on the left can not be omitted: t1->t2->t3 -> t1->t2->t3 would actually parse as t1->(t2->(t3->(t1->(t2->t3)))). That would be instead the type of
(\w x y w' x' -> y) :: t1 -> t2 -> t3 -> t1 -> t2 -> t3
└w └x └y └w' └x' └y
...preferrably written (\_ _ y _ _ -> y).

Confused with nested lambda types in haskell

Just trying to see the types of some lambda expressions like this one:
:t \x -> (\y -> x y)
\x -> (\y -> x y) :: (t1 -> t2) -> t1 -> t2
shouldn't the type here be t1->(t2->t1->t2) ?
Similarly
:t \x -> (\y -> (\k -> y (x k)))
\x -> (\y -> (\k -> y (x k)))
:: (t1 -> t2) -> (t2 -> t3) -> t1 -> t3
Shouldn't the type be t1->(t2->(t3->t2))?
:t \x -> (\y -> x y)
\x -> (\y -> x y) :: (t1 -> t2) -> t1 -> t2
shouldn't the type here be t1->(t2->t1->t2) ?
No, t1->(t2->t1->t2) is the same as t1->t2->t1->t2 which is the type of a three-arguments function (of type t1, t2, and t1) returning t2. However, there are only two lambdas, for the two arguments x and y.
The right type is instead
typeOfX -> (typeofY -> typeOfResult)
\x -> (\y -> x y)
(By the way, none of the parentheses above are needed.)
What is typeOfResult? Is is the type of x y, so it is the return type for x which must be a function.
In order for the code to type check, we must then have that typeOfX is a function type, say a -> b. In such case we can see that typeOfResult = b. Further, in x y we pass y to x, and this can type check only if typeOfY = a.
So,
typeOfX -> typeofY -> typeOfResult
=
(a -> b) -> a -> b
The compiler used names t1 and t2, but this is the same type.
Parentheses here matter, since we must remember that x is a function a -> b.
Without parentheses we would get a three-argument function, as explained above.
You can try to apply the same reasoning to the second example. Start from
typeOfX -> typeofY -> typeOfK -> TypeOfResult, and slowly discover what these types actually are.
The type of x in \x -> \y -> x y is t1 -> t2, and it's the first argument.
As the outermost lambda, it gets applied first, followed by y
You could've written it as \x y -> x y which is just function application in the natural order.

Meaning of different lambda functions and characters

At the moment I am learning Haskell, but I am struggling with the syntax of a few example. What do they exactly mean?
First: What is the difference between these two lambdas (-> \y and y)?
lambda1 = \x -> \y -> x + y
lambda2 = \x y -> x + y
Second: What does this mean? Is this a lambda that act as a "pseudo" list generator that generates a list with 3 elements. How can I create such a list?
lambda3 = [\x -> x+1, \x -> 2*x, \x -> x^2]
Third: What does the \_ exactly mean?
lambda4 = \_ -> (\x -> x+1, \() -> 'a')
lambda2 is syntactic sugar for lambda1. All of these are equivalent:
f = \x -> \y -> x + y
f = \x y -> x + y
f x = \y -> x + y
f x y = x + y
f x y = (+) x y
f x = (+) x
f = (+)
lambda3 is a list of unary functions on numbers. Each function has the type (Num a) => a -> a, so the list has type (Num a) => [a -> a]. You could produce a list of values from this with map or a list comprehension:
fs = [\x -> x+1, \x -> 2*x, \x -> x^2]
map (\f -> f 3) fs
map ($ 3) fs
[f 3 | f <- fs]
==
[4, 6, 9]
lambda4 uses pattern-matching syntax. For example, if you have a data type:
data Foo = Foo Int String
Then you can write a lambda that pattern-matches on it:
f = \ (Foo n s) -> concat (replicate n s)
f (Foo 3 "bar") == "barbarbar"
(But unlike case, there is no way to provide alternative patterns if Foo has multiple constructors.)
The _ pattern just says “accept a value and ignore it”, so lambda4 is a function that accepts an argument, ignores it, and returns a pair (2-tuple) of unary functions, the first of type (Num a) => a -> a and the second of type () -> Char, so its type is Num a => r -> (a -> a, () -> Char).
lambda4 = \_ -> (\x -> x+1, \() -> 'a')
lambda4 = \ignored -> (\x -> x+1, \() -> 'a')
(inc, getA) = lambda4 ()
inc 3 == 4
getA () == 'a'
Functions that ignore their arguments can be constructed with the const function, and operator sections ((+ 1)) are typically preferred over lambdas (\x -> x + 1), so you can also write the above as:
lambda4 = const ((+ 1), const 'a')
On your second question, lambda3 is just a bad variable name. this is a list of functions of type Num a => a -> a. You can verify that by typing the following in ghci:
:t [\x -> x+1, \x -> 2*x, \x -> x^2]
First: What is the difference between these two lambdas (-> \y and y)?
There is no difference. Both produce the same output for the same input, and since they're pure functions, you can be sure that they produce no external effects that you wouldn't see.
The difference lies in that the first lambda uses syntactic sugar for currying.
\x y -> x + y is equal to \x -> \y -> x + y. Now, don't you think it looks a lot like type signatures, such as foo :: Int -> Int -> Int ? ;)
It means that the function foo takes 2 Int and produces an Int.
Since I don't have a very precise answer for the 2nd…
Third: What does the \_ exactly mean?
It's a lambda function (\) to which is associated the _ variable. _ is used as a placeholder to say “I don't care about the content of this variable, I'm even going to give it a proper name”.
There is no -> y. The correct way to read this is
(\ x -> (\ y -> (x + y)))
As it happens, Haskell has "curried functions", which means that
\ x y -> (x + y)
just happens to be equivalent to the above.
lambda3 is a list which contains three elements. Each of those elements happens to be a function. Functions are data in Haskell; you can pass them as arguments, return them as results, stuff them into lists, etc.
lambda3 = [ (\x -> x+1) , (\x -> 2*x) , (\x -> x^2) ]
lambda4 = \_ -> (\x -> x+1, \() -> 'a')
The "_" character basically means "I don't care what this is; ignore it". You can use it anywhere you can use a pattern. For example,
foobar x _ z = x + y
is a 3-argument function that completely ignores argument #2. Read about pattern matching and this should become clear. (I.e., it's not to do with lambdas, it's to do with patterns.)

Is there a way to elegantly represent this pattern in Haskell?

Mind the pure function below, in an imperative language:
def foo(x,y):
x = f(x) if a(x)
if c(x):
x = g(x)
else:
x = h(x)
x = f(x)
y = f(y) if a(y)
x = g(x) if b(y)
return [x,y]
That function represents a style where you have to incrementally update variables. It can be avoided in most cases, but there are situations where that pattern is unavoidable - for example, writing a cooking procedure for a robot, which inherently requires a series of steps and decisions. Now, imagine we were trying to represent foo in Haskell.
foo x0 y0 =
let x1 = if a x0 then f x0 else x0 in
let x2 = if c x1 then g x1 else h x1 in
let x3 = f x2 in
let y1 = if a y0 then f y0 else y0 in
let x4 = if b y1 then g x3 else x3 in
[x4,y1]
That code works, but it is too complicated and error prone due to the need for manually managing the numeric tags. Notice that, after x1 is set, x0's value should never be used again, but it still can. If you accidentally use it, that will be an undetected error.
I've managed to solve this problem using the State monad:
fooSt x y = execState (do
(x,y) <- get
when (a x) (put (f x, y))
(x,y) <- get
if c x
then put (g x, y)
else put (h x, y)
(x,y) <- get
put (f x, y)
(x,y) <- get
when (a y) (put (x, f y))
(x,y) <- get
when (b y) (put (g x, x))) (x,y)
This way, need for tag-tracking goes away, as well as the risk of accidentally using an outdated variable. But now the code is verbose and much harder to understand, mainly due to the repetition of (x,y) <- get.
So: what is a more readable, elegant and safe way to express this pattern?
Full code for testing.
Your goals
While the direct transformation of imperative code would usually lead to the ST monad and STRef, lets think about what you actually want to do:
You want to manipulate values conditionally.
You want to return that value.
You want to sequence the steps of your manipulation.
Requirements
Now this indeed looks first like the ST monad. However, if we follow the simple monad laws, together with do notation, we see that
do
x <- return $ if somePredicate x then g x
else h x
x <- return $ if someOtherPredicate x then a x
else b x
is exactly what you want. Since you need only the most basic functions of a monad (return and >>=), you can use the simplest:
The Identity monad
foo x y = runIdentity $ do
x <- return $ if a x then f x
else x
x <- return $ if c x then g x
else h x
x <- return $ f x
y <- return $ if a x then f y
else y
x <- return $ if b y then g x
else y
return (x,y)
Note that you cannot use let x = if a x then f x else x, because in this case the x would be the same on both sides, whereas
x <- return $ if a x then f x
else x
is the same as
(return $ if a x then (f x) else x) >>= \x -> ...
and the x in the if expression is clearly not the same as the resulting one, which is going to be used in the lambda on the right hand side.
Helpers
In order to make this more clear, you can add helpers like
condM :: Monad m => Bool -> a -> a -> m a
condM p a b = return $ if p then a else b
to get an even more concise version:
foo x y = runIdentity $ do
x <- condM (a x) (f x) x
x <- fmap f $ condM (c x) (g x) (h x)
y <- condM (a y) (f y) y
x <- condM (b y) (g x) x
return (x , y)
Ternary craziness
And while we're up to it, lets crank up the craziness and introduce a ternary operator:
(?) :: Bool -> (a, a) -> a
b ? ie = if b then fst ie else snd ie
(??) :: Monad m => Bool -> (a, a) -> m a
(??) p = return . (?) p
(#) :: a -> a -> (a, a)
(#) = (,)
infixr 2 ??
infixr 2 #
infixr 2 ?
foo x y = runIdentity $ do
x <- a x ?? f x # x
x <- fmap f $ c x ?? g x # h x
y <- a y ?? f y # y
x <- b y ?? g x # x
return (x , y)
But the bottomline is, that the Identity monad has everything you need for this task.
Imperative or non-imperative
One might argue whether this style is imperative. It's definitely a sequence of actions. But there's no state, unless you count the bound variables. However, then a pack of let … in … declarations also gives an implicit sequence: you expect the first let to bind first.
Using Identity is purely functional
Either way, the code above doesn't introduce mutability. x doesn't get modified, instead you have a new x or y shadowing the last one. This gets clear if you desugar the do expression as noted above:
foo x y = runIdentity $
a x ?? f x # x >>= \x ->
c x ?? g x # h x >>= \x ->
return (f x) >>= \x ->
a y ?? f y # y >>= \y ->
b y ?? g x # x >>= \x ->
return (x , y)
Getting rid of the simplest monad
However, if we would use (?) on the left hand side and remove the returns, we could replace (>>=) :: m a -> (a -> m b) -> m b) by something with type a -> (a -> b) -> b. This just happens to be flip ($). We end up with:
($>) :: a -> (a -> b) -> b
($>) = flip ($)
infixr 0 $> -- same infix as ($)
foo x y = a x ? f x # x $> \x ->
c x ? g x # h x $> \x ->
f x $> \x ->
a y ? f y # y $> \y ->
b y ? g x # x $> \x ->
(x, y)
This is very similar to the desugared do expression above. Note that any usage of Identity can be transformed into this style, and vice-versa.
The problem you state looks like a nice application for arrows:
import Control.Arrow
if' :: (a -> Bool) -> (a -> a) -> (a -> a) -> a -> a
if' p f g x = if p x then f x else g x
foo2 :: (Int,Int) -> (Int,Int)
foo2 = first (if' c g h . if' a f id) >>>
first f >>>
second (if' a f id) >>>
(\(x,y) -> (if b y then g x else x , y))
in particular, first lifts a function a -> b to (a,c) -> (b,c), which is more idiomatic.
Edit: if' allows a lift
import Control.Applicative (liftA3)
-- a functional if for lifting
if'' b x y = if b then x else y
if' :: (a -> Bool) -> (a -> a) -> (a -> a) -> a -> a
if' = liftA3 if''
I'd probably do something like this:
foo x y = ( x', y' )
where x' = bgf y' . cgh . af $ x
y' = af y
af z = (if a z then f else id) z
cgh z = (if c z then g else h) z
bg y x = (if b y then g else id) x
For something more complicated, you may want to consider using lens:
whenM :: Monad m => m Bool -> m () -> m ()
whenM c a = c >>= \res -> when res a
ifM :: Monad m => m Bool -> m a -> m a -> m a
ifM mb ml mr = mb >>= \b -> if b then ml else mr
foo :: Int -> Int -> (Int, Int)
foo = curry . execState $ do
whenM (uses _1 a) $
_1 %= f
ifM (uses _1 c)
(_1 %= g)
(_1 %= h)
_1 %= f
whenM (uses _2 a) $
_2 %= f
whenM (uses _2 b) $ do
_1 %= g
And there's nothing stopping you from using more descriptive variable names:
foo :: Int -> Int -> (Int, Int)
foo = curry . execState $ do
let x :: Lens (a, c) (b, c) a b
x = _1
y :: Lens (c, a) (c, b) a b
y = _2
whenM (uses x a) $
x %= f
ifM (uses x c)
(x %= g)
(x %= h)
x %= f
whenM (uses y a) $
y %= f
whenM (uses y b) $ do
x %= g
This is a job for the ST (state transformer) library.
ST provides:
Stateful computations in the form of the ST type. These look like ST s a for a computation that results in a value of type a, and may be run with runST to obtain a pure a value.
First-class mutable references in the form of the STRef type. The newSTRef a action creates a new STRef s a reference with an initial value of a, and which can be read with readSTRef ref and written with writeSTRef ref a. A single ST computation can use any number of STRef references internally.
Together, these let you express the same mutable variable functionality as in your imperative example.
To use ST and STRef, we need to import:
{-# LANGUAGE NoMonomorphismRestriction #-}
import Control.Monad.ST.Safe
import Data.STRef
Instead of using the low-level readSTRef and writeSTRef all over the place, we can define the following helpers to match the imperative operations that the Python-style foo example uses:
-- STRef assignment.
(=:) :: STRef s a -> ST s a -> ST s ()
ref =: x = writeSTRef ref =<< x
-- STRef function application.
($:) :: (a -> b) -> STRef s a -> ST s b
f $: ref = f `fmap` readSTRef ref
-- Postfix guard syntax.
if_ :: Monad m => m () -> m Bool -> m ()
action `if_` guard = act' =<< guard
where act' b = if b then action
else return ()
This lets us write:
ref =: x to assign the value of ST computation x to the STRef ref.
(f $: ref) to apply a pure function f to the STRef ref.
action `if_` guard to execute action only if guard results in True.
With these helpers in place, we can faithfully translate the original imperative definition of foo into Haskell:
a = (< 10)
b = even
c = odd
f x = x + 3
g x = x * 2
h x = x - 1
f3 x = x + 2
-- A stateful computation that takes two integer STRefs and result in a final [x,y].
fooST :: Integral n => STRef s n -> STRef s n -> ST s [n]
fooST x y = do
x =: (f $: x) `if_` (a $: x)
x' <- readSTRef x
if c x' then
x =: (g $: x)
else
x =: (h $: x)
x =: (f $: x)
y =: (f $: y) `if_` (a $: y)
x =: (g $: x) `if_` (b $: y)
sequence [readSTRef x, readSTRef y]
-- Pure wrapper: simply call fooST with two fresh references, and run it.
foo :: Integral n => n -> n -> [n]
foo x y = runST $ do
x' <- newSTRef x
y' <- newSTRef y
fooST x' y'
-- This will print "[9,3]".
main = print (foo 0 0)
Points to note:
Although we first had to define some syntactical helpers (=:, $:, if_) before translating foo, this demonstrates how you can use ST and STRef as a foundation to grow your own little imperative language that's directly suited to the problem at hand.
Syntax aside, this matches the structure of the original imperative definition exactly, without any error-prone restructuring. Any minor changes to the original example can be mirrored directly to Haskell. (The addition of the temporary x' <- readSTRef x binding in the Haskell code is only in order to use it with the native if/else syntax: if desired, this can be replaced with an appropriate ST-based if/else construct.)
The above code demonstrates giving both pure and stateful interfaces to the same computation: pure callers can use foo without knowing that it uses mutable state internally, while ST callers can directly use fooST (and for example provide it with existing STRefs to modify).
#Sibi said it best in his comment:
I would suggest you to stop thinking imperatively and rather think in a functional way. I agree that it will take some time to getting used to the new pattern, but try to translate imperative ideas to functional languages isn't a great approach.
Practically speaking, your chain of let can be a good starting point:
foo x0 y0 =
let x1 = if a x0 then f x0 else x0 in
let x2 = if c x1 then g x1 else h x1 in
let x3 = f x2 in
let y1 = if a y0 then f y0 else y0 in
let x4 = if b y1 then g x3 else x3 in
[x4,y1]
But I would suggest using a single let and giving descriptive names to the intermediate stages.
In this example unfortunately I don't have a clue what the various x's and y's do, so I cannot suggest meaningful names. In real code you would use names such as x_normalized, x_translated, or such, instead of x1 and x2, to describe what those values really are.
In fact, in a let or where you don't really have variables: they're just shorthand names you give to intermediate results, to make it easy to compose the final expression (the one after in or before the where.)
This is the spirit behind the x_bar and x_baz below. Try to come up with names that are reasonably descriptive, given the context of your code.
foo x y =
let x_bar = if a x then f x else x
x_baz = f if c x_bar then g x_bar else h x_bar
y_bar = if a y then f y else y
x_there = if b y_bar then g x_baz else x_baz
in [x_there, y_bar]
Then you can start recognizing patterns that were hidden in the imperative code. For example, x_bar and y_bar are basically the same transformation, applied respectively to x and y: that's why they have the same suffix "_bar" in this nonsensical example; then your x2 probably doesn't need an intermediate name , since you can just apply f to the result of the entire "if c then g else h".
Going on with the pattern recognition, you should factor out the transformations that you are applying to variables into sub-lambdas (or whatever you call the auxiliary functions defined in a where clause.)
Again, I don't have a clue what the original code did, so I cannot suggest meaningful names for the auxiliary functions. In a real application, f_if_a would be called normalize_if_needed or thaw_if_frozen or mow_if_overgrown... you get the idea:
foo x y =
let x_bar = f_if_a x
y_bar = f_if_a y
x_baz = f (g_if_c_else_h x_bar)
x_there = g_if_b x_baz y_bar
in [x_there, y_bar]
where
f_if_a x
| a x = f x
| otherwise = x
g_if_c_else_h x
| c x = g x
| otherwise = h x
g_if_b x y
| b y = g x
| otherwise = x
Don't disregard this naming business.
The whole point of Haskell and other pure functional languages is to express algorithms without the assignment operator, meaning the tool that can modify the value of an existing variable.
The names you give to things inside a function definition, whether introduced as arguments, let, or where, can only refer to one value (or auxiliary function) throughout the entire definition, so that your code can be more easily reasoned about and proven correct.
If you don't give them meaningful names (and conversely giving your code a meaningful structure) then you're missing out on the entire purpose of Haskell.
(IMHO the other answers so far, citing monads and other shenanigans, are barking up the wrong tree.)
I always prefer layering state transformers to using a single state over a tuple: it definitely declutters things by letting you "focus" on a specific layer (representations of the x and y variables in our case):
import Control.Monad.Trans.Class
import Control.Monad.Trans.State
foo :: x -> y -> (x, y)
foo x y =
(flip runState) y $ (flip execStateT) x $ do
get >>= \v -> when (a v) (put (f v))
get >>= \v -> put ((if c v then g else h) v)
modify f
lift $ get >>= \v -> when (a v) (put (f v))
lift get >>= \v -> when (b v) (modify g)
The lift function allows us to focus on the inner state layer, which is y.

Writing Category Instance for custom Lens

I have been reading this article for understanding Lenses. I know this is different from
Edward Knett's lens package, but nonetheless it's useful for fundamentals.
So, A Lens is defined like this:
type Lens a b = (a -> b, b -> a -> a)
It has been mentioned that Lenses form a category and I have been
trying out to create an instance for Category typeclass. For a start, I
wrote the type definition for the functions:
(.) :: Lens y z -> Lens x y -> Lens x z
id :: Lens x x
And after this, I just stare it for all day. What exactly is the
thought process for writing it's definition?
I found this article (Lenses from Scratch on fpcomplete by Joseph Abrahamson) to be very good, it starts from the same representation of lenses you started with, defines composition for it and continues along the path to a representation more similar to lens
EDIT: I find type holes to be excellent when doing this kind of things:
(<.>):: Lens y z -> Lens x y -> Lens x z
(getA,setA) <.> (getB,setB) = (_,_)
So now we have 2 holes, the first in the tuple says (output cleaned):
Found hole ‘_’ with type: x -> z
...
Relevant bindings include
setB :: y -> x -> x
getB :: x -> y
setA :: z -> y -> y
getA :: y -> z
(<.>) :: Lens y z -> Lens x y -> Lens x z
Looking hard at the bindings, we already have what we need! getB :: x -> y and getA :: y -> z together with function composition (.) :: (b -> c) -> (a -> b) -> a -> c
So we happily insert this:
(<.>):: Lens y z -> Lens x y -> Lens x z
(getA,setA) <.> (getB,setB) = (getA . getB, _)
And continue with the second type hole, which says:
Found hole ‘_’ with type: z -> x -> x
Relevant bindings include
setB :: y -> x -> x
getB :: x -> y
setA :: z -> y -> y
getA :: y -> z
The most similar thing we have is setA :: z -> y -> y, we start by inserting a lambda, capturing the arguments:
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> _)
changing your type hole to:
Found hole ‘_’ with type: x
Relevant bindings include
x :: x
z :: z
setB :: y -> x -> x
getB :: x -> y
setA :: z -> y -> y
getA :: y -> z
we could insert x which type checks, but does not give us what we want (nothing happens when setting). The only other binding that could give us an x is setB, so we insert that:
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> setB _ _)
Our first type hole says:
Found hole ‘_’ with type: y
Relevant bindings include
x :: x
z :: z
setB :: y -> x -> x
getB :: x -> y
setA :: z -> y -> y
getA :: y -> z
So we need an y, looking at what is in scope, getB can give us a y if we give it a x, which we happen to have, but this would lead us to a useless lens doing nothing again. The alternative is to use setA:
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> setB (setA _ _) _)
(Speeding things a little up from here on)
Again the first hole wants something of type z which he happen to have as an argument to our lambda:
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> setB (setA z _) _)
To fill the first type hole of type y we can use getB :: x -> y giving it the argument of our lambda:
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> setB (setA z (getB x)) _)
Which leaves us with one remaining type hole, which can trivially be replaced by x, leading to the final definition:
(<.>):: Lens y z -> Lens x y -> Lens x z
(getA,setA) <.> (getB,setB) = (getA . getB, \z x -> setB (setA z (getB x)) x)
You can try to define id for yourself, using type holes and hoogle if necessary
Try this:
(.) :: Lens y z -> Lens x y -> Lens x z
(getZfromY , setZinY) . (getYfromX , setYinX) = (getZfromX , setZinX)
where getZfromX someX = ...
setZinX someZ someX = ...
The idea is: combine the two getters to make the new getter, and combine the two setters to make a new setter.
For the identity, think about:
id :: Lens x x
id = (getXfromX , setXinX)
where getXfromX someX = ...
setXinX newX oldX = ...
It seems to be a fairly straighforward process. But also need to check that you get a category - this requires equational reasoning - because, for example, there is at least one more way to implement the setter of id with type x->x->x - only one of those will make a category.
So, let's start with getting functions of the right type.
Lens y z -> Lens x y -> Lens x z ==
(y->z, z->y->y) -> (x->y, y->x->x) -> (x->z, z->x->x)
It seems clear how to get x->z from x->y and y->z - compose. Well, and you have ways to construct new x from old x and new y, and a way to get old y from old x, so if you can construct new y from z and old y, you are done.
(.) (yz, zyy) (xy, yxx) = (yz . xy, \z x -> yxx (zyy z (xy x)) x)
Similarly for id:
Lens x x ==
(x->x, x->x->x)
So
id = (id, const)
So far so good, the types check. Now let's check that we've got a category. There is one law:
f . id = f = id . f
Checking one way (a bit informal, so need to bear in mind that . and id refer to different things in f . id and fg . id):
f . id = (fg, fs) . (id, const) =
(fg . id, \z x -> const (fs z (id x)) x) =
(fg, \z x -> fs z (id x)) = (fg, fs)
Checking the other way:
id . f = (id, const) . (fg, fs) =
(id . fg, \z x -> fs (const z (fg x)) x) =
(fg, \z x -> fs z x) = (fg, fs)

Resources